Psychotherapist Interventions Coding System (PICS): A systematic analysis of rhetoric mechanisms in psychotherapy. - Herrero, Olga; Aulet, Adriana; Botella, Lluís; Alves, Daniela; Rosa, Catarina (Narrative Inquiry, 2019)
The aim of the present study is to reformulate a descriptive typology previously developed with grounded theory as a result of the qualitative analysis of a good outcome case study. We developed a transtheoretical and easily usable coding system. We describe the developing process of this new coding system, which is focused on the use of language by the psychotherapist. Four researchers were discussing every stage and basing decisions on consensus. As a result, we have developed the Psychotherapist Interventions Coding System (PICS). The resultant coding system is described within 4 group of macro categories: (1) Discursive contract; (2) Facilitators of the therapeutic relationship (3) Facilitators of the client's speech; and (4) Liberation of constraining speeches. The PICS aims to contribute to developing knowledge on research and how therapist interventions contribute within psychotherapeutic processes, acknowledge the kind of interventions therapists are using in the sessions and assist teaching on novel therapists in training programs.